Clinical skills boot camp in a program to train healthcare professionals to provide primary care to underserved communities - Wu, Helen; Mansilla-Rivera, Kenia; Wang, Biju; Clark-Dufner, Petra; Pugh Yi, Robin; Gould, Bruce (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Implication StatementThis article describes the evaluation of a clinical skills boot camp for students at Connecticut Area Health Education Center (CT AHEC) interdisciplinary program to train primary healthcare professionals to serve underserved communities. Early intensive training in basic clinical knowledge can ensure students begin programs with shared basic knowledge, which can facilitate skills in delivering team-based care, a key strategy for optimizing primary healthcare workforce capacity and efficiency.